Clinical outcomes of COVID-19 infection in congenital heart disease: A single-center experience in Indonesia - Siagian, Sisca Natalia; Oetama, Susandy; Pohan, Fathy Zuandi; Mendel, Brian; Lelya, Olfi; Sakti, Damba Dwisepto Aulia; Kurniawati, Yovi (Frontiers in Cardiovascular Medicine, 2022)
Background Congenital heart disease (CHD) patients are thought to be vulnerable to COVID-19 complications. In this study, we would like to assess the outcomes and clinical characteristics in COVID-19 CHD patients. Method A single-center, observational study was conducted in National Cardiovascular Center Harapan Kita (NCCHK). This study included patients with CHD who were hospitalized for COVID-19. The extracted data were baseline characteristics, clinical findings, supportive examination findings, complications, outcomes, and length of stay of the patients. The data were then analyzed using SPSS 26.0 software. Result Twenty-six patients with CHD and COVID-19 infection were included in our study. There were 24 resolved cases and 2 deaths, four patients experienced complications such as renal insufficiency (1), sepsis (2), and multiorgan failure (1). The median length of stay was 13 days. The most common symptoms experienced by the patients were breathlessness (65.4%), cough (57.7%), and fever (42.3%). Conclusion We observed a relatively mild COVID-19 clinical course despite prior research showing that patients with cardiovascular comorbidities, such as CHD, have a higher case-fatality rate. This could be because of the smaller sample size, non-standardized diagnosis, severity, treatment, and age group.